1989
DOI: 10.3758/bf03208152
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with increased Weber ratios

Abstract: To investigate whether age-associated changes in the human taste system are quality-specific, we compared young and elderly subjects' suprathreshold discrimination abilities for caffeine and sucrose. The method of constant stimuli was used to obtain just noticeable differences and Weber ratios. The elderly generated larger Weber ratios than did the young for both the medium and high concentrations of caffeine, but not for the low concentration. For example, a 74% increase in .005M caffeine was required to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 20 publications
2
25
1
1
Order By: Relevance
“…Overall, only three samples (nonbarium water, nonbarium sucrose, and barium sucrose) were liked by subjects, as indicated by positive mean palatability scores. These data are consistent with previous evidence that sweet taste tends to elicit a greater pleasure response than other taste qualities across the human lifespan [61–64], apparently even in the presence of barium. Higher refusal rates for barium samples reinforced the palatability score results, in that the samples with the lowest palatability scores tended to be most frequently refused.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, only three samples (nonbarium water, nonbarium sucrose, and barium sucrose) were liked by subjects, as indicated by positive mean palatability scores. These data are consistent with previous evidence that sweet taste tends to elicit a greater pleasure response than other taste qualities across the human lifespan [61–64], apparently even in the presence of barium. Higher refusal rates for barium samples reinforced the palatability score results, in that the samples with the lowest palatability scores tended to be most frequently refused.…”
Section: Discussionsupporting
confidence: 92%
“…When using aqueous solutions with a sucrose concentration of 3 and 6 g/100 g, the response of our panel resulted in k = 0.060 and k = 0.057 (no vanilla flavor), and in k = 0.057 and k = 0.062 (with vanilla flavor), respectively. These fractions are close to those presented by Lundgren, Pangborn, Barylko-Pikielna, and Daget (1976) and Berg, Filipello, Hinreiner, and Webb (1955), whereas about twice as high Weber fractions for sucrose sweetness have been published by, e.g., Gilmore and Murphy (1989), McBride (1983) and Laing et al (1983). Weber ratios for sucrose sweetness in water as low as 0.075 have also been quantified for nonhuman primates (Laska, Scheuber, Carrera Sachez, & Rodriguez Luna, 1999).…”
Section: Resultssupporting
confidence: 50%
“…Seventeen studies found taste-identification thresholds to increase with age, although one study reported only a weak relationship between age and taste strip results (52) . Only one study found no significant difference between age groups (53) ; however, their older group was younger than in all other studies reported in this review (age [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and therefore outside of our inclusion criteria. (27) 18 34 37 65-78 55-65 ME NaCl, SU (6) NaCl P < 0 .…”
Section: Effects Of Ageing On Taste Identification Thresholdscontrasting
confidence: 58%